(untitled) (Medico Legal Update, 2019)
The objective is to propose a cloud hospital information system (cHIS) to allow small and medium sized hospitals to provide smart healthcare services and gain improved competitiveness. The research was conducted on cloud platform-based HIS service, mobile electronic medical record (EMR) service, personal biological record (PBR) service and healthcare big data service. Cloud computing technology was used for the HIS service to minimize the operating cost, IoT was applied to the mobile EMR and PBR services, and big data technology was used for the healthcare big data service to raise the efficiency in the clinical setting. This study examined the measures for promoting the use of cloud computing technology in the healthcare sector. If service providers can provide affordable, high-quality cloud healthcare services, such services will become high in demand despite hindrances. Thus, the architecture and service model of the cHIS were designed to minimize the operating costs through resource pooling achieved by virtualizing the hardware and application programs to promote affordability. Also, CloudSim was used to assess the stability and efficiency in relation to the data access time, service processing time and service wait time. First, the results of the experiment showed that an increase in the cloud storage disk and network bandwidths allows more users to be serviced. Second, it was found that the packet size had little to no impact on the system performance. Third, it was found that cloud-based distributed storage and processing was more efficient than using a web-based database in case of processing large amounts of data. The system presents economic advantages including maximized sharing of resources and minimized costs, enables real-time exchange of healthcare data, and promotes the use of collective intelligence for better healthcare services.